Antifungal Activity of Plant Latex collected from Plumeria alba L. , Tabernaemontana divaricata Linn. and Wrightia tinctoria R. Br. (International Journal of Food and Nutritional Sciences, 2022)
The creation of new chemotherapeutic drugs can benefit greatly from the structures found inmedicinal plants. The goal of the current investigation was to assess the antifungal activity oflatex extract from Plumeria alba L. , Tabernaemontana divaricata Linn. and Wrightia tinctoria R. Br. that has been partially purified against a few pathogenic fungi isolated from various fruits. In vitro tests were done on the latex's ethanolic extract against various fungus strains. The disc diffusion method was used to evaluate the inhibitory impact. The serial dilution approach was also used to calculate the minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC). A qualitative phytochemical screening was performed on the ethanolic extract to check for the presence of any bioactive components. Numerous physiologically active compounds, including Flavonoids, alkaloids, terpenoids, steroids, saponins, phenols, and glycosides are present in the ethanolic extract. The latex extract exhibits a considerable, dose-dependent zone of inhibition. The Latex extract's MIC and MFC values range from 1 mg to 8 mg, and the outcomes are comparable to those of amphotericin B. We conclude from this research that latex extract has a high antioxidant capacity,fungicidal activity, which may be because of the ethanolic extract of Plumeria alba L. , Tabernaemontana divaricata Linn. and Wrightia tinctoria R. Br. latex contain biologically active components with antimicrobial activity.Plant latex bioactive chemicals have the potential to be a source of antifungals for infections that emerge after harvest. Different plant species' latexes were examined to determine their phytochemical and antifungal compositions. Alkaloids, flavonoids, glycosides, phenols, saponins, steroids, tannins, and terpenoids were found in latex extracts after analysis with phytochemical tests. Petroleum ether extracts may have an inhibitory effect against the postharvest fungus isolates, according to an antifungal experiment. Different levels of sensitivity were seen regardless of the plant species. In conclusion, using plant latex to manage post-harvest fungal infections is interesting and fits well with the idea of environmental and human health safety.